(untitled) (Journal of Transport System Engineering, 2019)
In helicopter performance, tail shake phenomenon plays an important role as it can affect overall performance, occupant comfort and handling qualities of helicopter. The objective of this undergraduate project is to conduct wind tunnel tests to investigate pressure characterisation on standard helicopter fuselage. The flows of wind and pressure contour were recorded. In this experimental research work, a simplified NASA standard fuselage model was mated to a main-rotor-hub assembly from a remote-control helicopter. The model was equipped with 28 pressure taps and the locations of the taps were determined by past year studies. Data of pressure corresponding to the variations of helicopter’s pylon configurations and advance ratios were recorded by using Electronic Pressure Scanning System. The effects of advances ratio and pylon configuration to pressure distribution around helicopter fuselage were analysed. This work had gained some useful information towards understanding of this helicopter tail shake phenomenon and will help in the open literature in helicopter’s tail shake matters.